Implementation Of Marugame Udon Promotion Strategy Through ‘FOMO’ (Fear Of Missing Out) Behavior - Mohamad Rozan Baariq Mardison (UNIVED Press, 2025)
This study aims to examine the marketing promotion strategy of Marugame Udon through event and local store promotion strategies. This study focuses on the extent to which these factors can cause FOMO (Fear Of Missing Out) behavior in Marugame Udon consumers. This study uses a qualitative approach using primary data through interviews with the analysis unit. The data collected is then presented descriptively. The findings of this study indicate that the marketing promotion strategy through events and local store marketing can cause FOMO (Fear Of Missing Out) behavior in potential consumers. The implementation of the results of this study is that Marugame Udon can increase the frequency of events and local store promotions to attract the attention of more potential consumers. In addition, Marugame Udon can utilize social media to inform the event widely, so that it can create a higher sense of FOMO among consumers.